Demonstration of K-0(K)over-bar(0), B-0(B)over-bar(0) and D-0(D)over-bar(0) transitions with a pair of coupled pendula - Schubert, Klaus R.; Stiewe, Jürgen (Journal of physics. G, Nuclear and particle physics, 2011)
A setup of two coupled and damped pendula is used to demonstrate the main features of transitions between the neutral mesons K 0 , D 0 , B 0 and their antiparticles, including CP violation in the K 0 system. The transitions are described by two-state Schrödinger equations. Since the real parts of their solutions obey the same differential equations as the pendula coordinates, the pendulum motions can be used to represent the meson transitions. Movie clips of the motions are available as supplementary material.
Gesehen am 13.04.2018